Opioid prescribing on discharge to skilled nursing facilities. Issue 9 (29th July 2020) - Hubsky, Ashlee R.; Noble, Brie N.; Hartung, Daniel M.; Tjia, Jennifer; Lapane, Kate L.; Furuno, Jon P.
Abstract: Purpose: Skilled nursing facility (SNF) residents are at increased risk for opioid‐related harms. We quantified the frequency of opioid prescribing among patients discharged from an acute care hospital to SNFs. Methods: This was a retrospective cohort study among adult (≥18 years) inpatients discharged from a quaternary‐care academic referral hospital in Portland, OR to a SNF between January 1, 2017 and December 31, 2018. Our primary outcome was receipt of an opioid prescription on discharge to a SNF. Our exposures included patient demographics (eg, age, sex), comorbid illnesses, surgical diagnosis related group (DRG), receiving opioids on the first day of the index hospital admission, and inpatient hospital length of stay. Results: Among 4374 patients discharged to a SNF, 3053 patients (70%) were prescribed an opioid on discharge. Among patients prescribed an opioid, 61% were over the age of 65 years, 50% were male, and 58% had a surgical Medicare severity diagnosis related group (MS‐DRG). Approximately 70% of patients discharged to a SNF were prescribed an opioid on discharge, of which 68% were for oxycodone, and 52% were for ≥90 morphine milligram equivalents per day. Surgical DRG, diagnoses of cancer or chronic pain, last pain score, and receipt of an opioid on first day of the index hospital admission were independently associated with being prescribed an opioid on discharge to a SNF. Conclusion: Opioids were frequently prescribed at high doses to patients discharged to a SNF. Efforts to improve opioid prescribing safety during this transition may be warranted.